SOME EFFECTS OF ZOOTOPIA MOVIES ON VOCABULARY MASTERY OF THE JUNIOR SECONDARY STUDENTS - Tutty Tazkiyah Umar; Sahril Nur; Muh. Tahir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The aims of this research were to discover whether some effects of Zootopia movies on vocabulary mastery of the junior secondary students in vocabulary teaching have an effect or not. The pre-experimental design was the method used by the researchers with one class pre-test and post-test. The secondary students were the population of MTsN Kota Parepare in the 2021/2022 academic year. The sample was taken with a cluster random sampling technique that consisted of 25 students. The instrument of this research was a vocabulary test administered as a pre-test and post-test. This research found a substantial difference in students' scores before and after treatment. As can be observed from the mean score, students' pre-test means score was (53,24), which was lower than their post-test mean score (85,96). The significant value of this research (0.000) was lower than the significant level (0.05). Therefore, the use of Zootopia Movie as a teaching media can increase students’ vocabulary mastery of the secondary students of MTsN Kota Parepare. The result of rxy is -0,461, and after being consulted to the table, rxy (- 0,461) is very weak. It means that the correlation is negative, using the Zootopia movie as a teaching media. In this case, the researchers conclude that there is a negative correlation between vocabulary test and students' responses using the Zootopia movie as a teaching media at secondary students of MTsN Kota Parepare.